2012
DOI: 10.1039/c1fd00069a
|View full text |Cite
|
Sign up to set email alerts
|

How is the water molecule activated on metalloporphyrins? Oxygenation of substrates induced through one-photon/two-electron conversion in artificial photosynthesis by visible light

Abstract: The reaction mechanism of the highly efficient (phi = 0.60), selective photochemical epoxidation of alkenes sensitized by CO-coordinated tetra(2,4,6-trimethyl)phenylporphyrinatoruthenium(II) (Ru(II)TMP(CO)), with water acting both as an electron and oxygen atom donor, was investigated. The steady-state light irradiation of the reaction mixture indicated the formation of the Ru(II)TMP (CO) cation radical under neutral conditions, which was effectively trapped by an hydroxide ion to regenerate the starting sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…Importantly, we believe that the studies presented here using a novel supramolecular assembly have expanded the types of molecules that could serve as candidates for efficient energy-transfer systems, such as in an artificial lightharvesting system. This light-harvesting system, when combined with the photochemical reactions where water molecules serve as electron and oxygen donors, 38 will open a new door to realizing the construction of new types of artificial photosynthetic systems.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Importantly, we believe that the studies presented here using a novel supramolecular assembly have expanded the types of molecules that could serve as candidates for efficient energy-transfer systems, such as in an artificial lightharvesting system. This light-harvesting system, when combined with the photochemical reactions where water molecules serve as electron and oxygen donors, 38 will open a new door to realizing the construction of new types of artificial photosynthetic systems.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Both free-base ligands and metalloporphyrins proved to be efficient for such reactions. In earlier and more recent works, cycloalkenes were effectively functionalized in such reactions, using porphyrin complexes of various transition metal ions [1][2][3][4][5][6]. Also, some aromatic (and aliphatic) alcohols and aldehydes were oxidized to carboxylic acids by solar irradiation of a Sb(V)-porphyrin [7].…”
Section: Introductionmentioning
confidence: 99%
“…For the most promising molecular catalyst for the one-electron oxidation-initiated water oxidation on the basis of our previous work, we prepared the water-soluble aluminump orphyrin,c ationic tetra-methylpyridiniumylporphyrinatealuminum (AlTM-PyP). [10,11] The structure is shown in Scheme 1. AlTMPyP has two water molecules as the axial ligands in water (Figure S1 ehi nt he Supporting Information) and exhibits protolytic equilibria among five speciesw ith different protonated or deprotonated axial ligands [11] (Figure S1 a-d).…”
Section: Resultsmentioning
confidence: 99%
“…In these context, we have been studying the two-electron oxidativea ctivation of water initiated by ap hotochemical one-electrono xidation of ac atalyst in the presence of an alkene to form oxygenated products such as epoxides. [10] Recently,w ealso found that earth-abundant main group elements such as Sn, Al, and Si also induced the photooxygenation of alkenes with water as both electron donor and oxygen-atom donor. [11] On the basis of those studies, we developed as tudy about electrochemical water splitting catalyzed by main group metal complexes and have now succeeded in generating hydrogen peroxide very efficiently with at urnover frequency up to~2 10 4 s À1 by aone-electron oxidation-initiated two-electron oxidationo fw ater catalyzed by aluminum porphyrins incorporating earth's most abundant metal as the central ionwith the lowest knownoverpotential (97 mV).…”
Section: Introductionmentioning
confidence: 99%